X-rays for Archaeology
IX, 308 p.
Keywords: The application of X-rays to archaeological objects with the goal of gaining insight into both their construction and chemical composition, in a non-destructive manner, dates back to the discovery of radiation. Nowadays, X-ray techniques, such as X-ray fluorescense and diffraction are standard tools. This book offers physicists, art historians, archaeologists, curators, and conservators a detailed overview via contributions written by leading scientists in the field. The book contains scientific data, i.e. in situ measurement data taken with portable XRF and XRD, and fine data taken with accelerating ion beams and synchrotron radiations, together with their explanations. Results obtained by traditional scientific methods are also reviewed. The broad data collection spans experimental data taken both from monuments in the field and exhibits in museums, for example: ancient Egyptian wall-painting pigments ancient Egyptian wooden statues and mummies ancient Greek funerary monuments Cypriot ceramics medieval, Lyubliana and Venetian glass Romanian ceramics ancient Near-Eastern clay old Japanese porcelain pre-Hispanic items from America ancient Chinese underglaze-red blue and white porcelain Chinese celadon Phoenician cosmetics Also included are data from glazes, ancient gold and silver coins, gold jewelleries, gold alloys, corroded metals, gemstones (ruby, emerald and garnet), painting pigments, pottery, bronze, obsidian, stucco, turquoise, and so on. The discussion fostered here between natural scientists and archaeologists anticipates the future direction of archaeology.